Comparing Google Scholar and Conventional Databases in Supporting Research on Academic Women’s Experiences of Bullying - Kamran, Roshana; Burns, Edgar A. (CV. Literasi Indonesia, 2025)
The search engine effectiveness of Google Scholar retrieval was compared with a cluster of well-known academic databases in conducting a scoping review for a project about women being bullied and harassed by academic colleagues. The literature research found broad similarities between the number of relevant articles retrieved from the group of academic databases and the results retrieved by Google Scholar. There were, however, three qualitative differences in how results were achieved that reduced the benefits of using Google’s free and single search engine: mixed relevance of results, the necessity for filtering non-relevant returned items, and the need for additional search practices. Learning how to achieve these results suggests a combined approach may still be the most convenient option for thorough literature searching at present. Even before Google Scholar’s limitations are addressed, however, its reach, speed, and accessibility outside paywalls open new possibilities as a primary search engine to gather scholarly material for marginalized communities, voluntary human service groups, and educational institutions with limited financial resources in both developed and developing societies. The present article provides one contribution to debates about the relative practical value of academic search engine options for gathering research literature compared with Google Scholar.